2008
DOI: 10.1038/nature07592
|View full text |Cite
|
Sign up to set email alerts
|

Enantiodivergent conversion of chiral secondary alcohols into tertiary alcohols

Abstract: From receptors in the nose to supramolecular biopolymers, nature shows a remarkable degree of specificity in the recognition of chiral molecules, resulting in the mirror image arrangements of the two forms eliciting quite different biological responses. It is thus critically important that during a chemical synthesis of chiral molecules only one of the two three-dimensional arrangements is created. Although certain classes of chiral molecules (for example secondary alcohols) are now easy to make selectively in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
177
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 396 publications
(184 citation statements)
references
References 28 publications
2
177
0
3
Order By: Relevance
“…We therefore tested enantioenriched, benzylic 40,41 and non-benzylic 42 tertiary boronic esters 1k-n in our process ( Table 2) and found that the desired products 2k-n were obtained in good yields and complete stereospecificity, demonstrating the power of the new methodology. As these boronic esters were readily prepared in essentially enantiopure form, the furyl-coupled products were also obtained in similarly enantiopure form as well.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore tested enantioenriched, benzylic 40,41 and non-benzylic 42 tertiary boronic esters 1k-n in our process ( Table 2) and found that the desired products 2k-n were obtained in good yields and complete stereospecificity, demonstrating the power of the new methodology. As these boronic esters were readily prepared in essentially enantiopure form, the furyl-coupled products were also obtained in similarly enantiopure form as well.…”
Section: Resultsmentioning
confidence: 99%
“…A range of enantioenriched secondary 39 and tertiary boronic esters [40][41][42] were then prepared by lithiation-borylation methodology or by hydroboration ( Figure 2, see SI for details) and subsequently tested under these optimized reaction conditions (Table 1). Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Among the challenges found in the stereoselective synthesis of organic molecules, it is included the development of low cost ligands and catalysts. [1][2][3][4] Here we report our results involving the addition of diethylzinc to aryl aldehydes using β- …”
Section: Introductionmentioning
confidence: 99%
“…Nun, da die Reaktivität von Organoborverbindungen in aufeinanderfolgenden Suzuki-Miyaura-Kupplungen eingestellt werden kann, sollte dieses Konzept zahlreiche Anwendungen finden, etwa in der Tandemkatalyse und der asymmetrischen Synthese. [11] Solche Studien werden außerdem Untersuchungen zur Einstellung der Reaktivität von anderen metallorganischen Verbindungen durch maßgeschneiderte Liganden anregen. [12] Diese Vorschriften sollten leistungsfähige Reagentien für die Synthese von Naturstoffen und hochmolekularen p-konjugierten Oligomeren mit genau definierter Struktur liefern und werden so zu Fortschritten in benachbarten Wissenschaftsgebieten beitragen.…”
unclassified